2015
DOI: 10.18335/region.v2i1.32
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel path analysis of social networks and social interaction in the neighbourhood

Abstract: Abstract. Neighborhood-based social interactions have gained attention as a research topic in recent decades in light of urban policies that aim to improve livability in urban areas. Social interactions are anticipated to play an important role in neighborhood livability; however, empirical studies investigating the extent to which neighborhood characteristics can improve social contacts among residents are scarce and inconclusive. Therefore, this paper studies the role of socio-demographics and neighborhood c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
4
14
0
Order By: Relevance
“…Age is found to have a significant effect on number of social interactions which is in line with the studies of Forrest and Kearns (2001) [ 66 ], Van Den Berg (2015) [ 42 ] and Moor and Mohammadi (2019) [ 43 ]. The oldest group (55 and older) recorded the lowest number of social interactions.…”
Section: Analyses and Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Age is found to have a significant effect on number of social interactions which is in line with the studies of Forrest and Kearns (2001) [ 66 ], Van Den Berg (2015) [ 42 ] and Moor and Mohammadi (2019) [ 43 ]. The oldest group (55 and older) recorded the lowest number of social interactions.…”
Section: Analyses and Resultssupporting
confidence: 87%
“…Age is found to have significant influence on the number of social interactions. Older people are less likely to interact with neighbors compared to younger age residents [ 42 , 43 ]. Home ownership [ 44 ] and length of residence [ 45 , 46 ] are positive indicators that increase social interaction between neighbors.…”
Section: Literaturementioning
confidence: 99%
“…This method is able to simultaneously analyze relationships between several dependent and independent variables, which is required for this study. Another of the advantages of a multi-level path model is that this approach is able to take into account the hierarchical structure of the data (multiple momentary experiences per participant, which have to be treated as clusters) [73]. The multi-level path model was estimated using the statistical software package LISREL version 8.54 [74].…”
Section: Methodsmentioning
confidence: 99%
“…To build the model structure, a stepwise model selection was used by adding independent variables (categorical variables were recoded into dummy variables) and their relationships that were expected to have a relationship based on the literature review and found to be significant using bivariate analyses. Correlations of personal characteristics and experience characteristics are allowed in the model [73]. To reduce the number of variables in the path analysis and not overfitting the model, the links that were not found to be significant in the path model, at the 0.05 significance level ( t ≥ 1.96), were subsequently removed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation